Pembelajaran Komunikasi, Motivasi Dan Muhasabah Untuk Guru, Siswa Dan Mahasiswa Di Masjid Al Muhajirin Perum Telaga Harapan Cikarang Barat Kabupaten Bekasi - Saktisyahputra Saktisyahputra (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
Learning communication and motivation of a teacher, student and student is one of the important components in the teaching and learning process. This skill development should be possessed by a teacher, student and student by involving various community activities with Communication Skill and Motivation.Carrying the theme